Spin polarized electronic reflections at metal-oxide interfaces: A technique for characterizing tunneling barriers in magnetic random access memory devices - Ounadjela, K; Da Costa, V; Iovan, A; Dimopoulos, T; Dahmani, F; Mahenthiran, D; Dieny, B; Allen, W; Gregg, J (2002)
One of the most critical steps in the realization of high quality tunneling devices is the fabrication of ultrathin oxide layers. This article describes a powerful technique for controlling the oxidation of ultrathin metallic layers. The technique consists of depositing the metallic layer to be oxidized on top of the soft magnetic layer of a bottom spin valve. The oxidation kinetics are then monitored by measuring the current in plane sheet resistance and magnetoresistance. The technique relies on the extreme sensitivity of the magnetoresistance on the degree of specular reflection at the soft magnetic layer/oxide interface. (C) 2002 American Institute of Physics.